Chronic stress and its effects on adrenal cortex apoptosis in pregnant rats - Bozzo, Aida Andrea (2013)
The model of chronic intermittent stress by immobilization during pregnancy may produce alterations in the mechanisms that maintain adrenal gland homeostasis. In earlier investigations using this model, signifi cant variations in plasma prolactin and corticosterone levels, and adrenal gland weights were observed. We hypothesized that chronic stress causes changes in apoptosis in the adrenal glands of pregnant rats. We identifi ed and quantifi ed apoptotic cells in the adrenal cortex and examined their ultrastructural characteristics using transmission electron microscopy. Adrenal glands of pregnant rats at gestation days 12, 17 and 21 were studied for control and experimental (stressed) rats. Immunolabelling techniques, stereological analysis and image quantifi cation of adrenal gland sections were combined to determine differences in apoptosis in the different cell populations of the adrenal cortex. The apoptotic index of the experimental rats showed a signifi cant reduction at gestation day 17, while at days 12 and 21 there were no differences from controls. Moreover, the apoptotic index of the reticular zones in control and experimental animals showed a signifi cant increase compared to the glomerular and fascicular zones at the three gestation times studied. Chronic stress by immobilization reduced the caspase-dependent apoptotic index at gestation day 17, which may be related to variations in plasma concentrations of estrogens and prolactin.